Synthesis, Antibacterial and Antifungal Activity of N’-(3-Hydroxy-4-Methoxy Benzylidene) Adamantane-1-Carbohydrazide (IVAC) and Its Isomers - Parab, D. D.; Kohli, H. K. (Journal of Scientific Research, 2025)
Novel 1-adamantyl derivatives were designed, synthesized and evaluated for anti-bacterial activity against Gram-negative bacteria, Escherichia coli, Gram-positive bacteria, Staphylococcus aureus, Bacillus subtilis and for antifungal activity against pathogen Candida albicans. The screening results indicated that the synthesised compounds N’-(3-hydroxy-4-methoxy benzylidene) adamantane-1-carbohydrazide (IVAC) and its isomers exhibited substantial antibacterial and antifungal properties when compared with known drug Ampicillin. The Minimum inhibitory concentration, MIC value obtained was less than 1.95 μg/ml. The structural features of IVAC and its isomers were confirmed by 1H-NMR, FTIR, and elemental analysis.